2015
DOI: 10.1088/0957-4484/26/16/161001
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide nanoflakes incorporated gelatin–hydroxyapatite scaffolds enhance osteogenic differentiation of human mesenchymal stem cells

Abstract: In this study, graphene oxide (GO) nanoflakes (0.5 and 1 wt%) were incorporated into a gelatin-hydroxyapatite (GHA) matrix through a freeze drying technique and its effect to enhance mechanical strength and osteogenic differentiation was studied. The GHA matrix with GO demonstrated less brittleness in comparison to GHA scaffolds. There was no significant difference in mechanical strength between GOGHA0.5 and GOGHA1.0 scaffolds. When the scaffolds were immersed in phosphate buffered saline (to mimic physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(98 citation statements)
references
References 37 publications
4
86
0
2
Order By: Relevance
“…Von Kossa staining was not observed in the control cultures without any particles or composites. These results imply that the late stage marker of osteogenic differentiation was enhanced by the synergistic effect of rGO nanosheets and HAp microparticles without the addition of osteogenic factors [63,64]. Recently, it has been revealed that gelatinfunctionalized GO can be efficiently used for the biomimetic mineralization of HAp, leading to promote the osteogenic differentiation of MC3T3-E1 preosteoblasts [65].…”
Section: Effects Of Rgo/hap Composites On Calcium Deposition and Matrmentioning
confidence: 91%
“…Von Kossa staining was not observed in the control cultures without any particles or composites. These results imply that the late stage marker of osteogenic differentiation was enhanced by the synergistic effect of rGO nanosheets and HAp microparticles without the addition of osteogenic factors [63,64]. Recently, it has been revealed that gelatinfunctionalized GO can be efficiently used for the biomimetic mineralization of HAp, leading to promote the osteogenic differentiation of MC3T3-E1 preosteoblasts [65].…”
Section: Effects Of Rgo/hap Composites On Calcium Deposition and Matrmentioning
confidence: 91%
“…Moreover, the coating with modified GO offered resistance to corrosion and it was also possible to increase the elastic module of HAp and fracture toughness [117,118]. Incorporation of GO nanoflakes in the scaffolds of gelatin and HAp produced compressive strengths and the yield was also increased compared to gelatin/HAp [119].…”
Section: Graphene In Biomedical Implantationmentioning
confidence: 99%
“…Nair et al [56] incorporated graphene oxide into gelatin/hydroxyapatite scaffolds to enhance the osteogenic differentiation of human mesenchymal stem cells. MSC’s on the scaffolds were cultured in two different culture conditions (media with and without osteogenic supplement) for quantitative evaluation of proliferation and osteogenic differentiation.…”
Section: Natural Vs Synthetic Biomaterialsmentioning
confidence: 99%
“…The results suggested that the cell proliferation on day 21 was reduced not due to the apoptosis/necrosis of cells. The graphene oxide scaffolds without the addition of osteogenic supplements, enhanced the proliferation and osteogenic differentiation of human mesenchymal stem cells [56]. Graphene oxide combined with silk fiber scaffolds are used for biomedical application and tissue engineering and the addition of graphene oxide has been shown to enhance the proliferation of MC3T3-E1 osteoblast cells when combined with silk fiber scaffolds.…”
Section: Natural Vs Synthetic Biomaterialsmentioning
confidence: 99%